Space and the Dynamic Between Openness and Closure: Open strategizing in the TV series Borgen. Issue 1 (January 2023) - Holstein, Jeannie; Rantakari, Anniina
In this paper we examine how the use of space shapes the dynamic between openness and closure in open strategizing. To do this, we draw from research that has defined organizational space as a process that is both a social product and produces social relations. We analysed the use of space in open strategizing in the Danish TV series and political drama Borgen . In our analysis we focused on three building blocks of space: boundaries, distance and movement, that allowed us to elaborate how the dynamic between openness and closure is shaped. Drawing on our analysis, we revealed three spatial features – physical visibility, strategizing artefacts, discursive designation – that play a role in the dynamic between openness and closure in strategizing. We constructed a conceptual framework that shows how these spatial features, and their different combinations, are associated with pivots between openness and closure. Thus, our findings advance prior open strategy research by providing potential explanations of why openness turns to closure, despite the attempts to keep the strategizing process open. We argue that taking space seriously provides a more nuanced understanding to some of the contingencies and possibilities related to the dynamics of openness and closure in strategizing.